Prevalence of the oral pathogen Filifactor alocis and its FtxA toxin related to clinical parameters and presence of Aggregatibacter actinomycetemcomitans - Zeinab Razooqi; Nabil Khzam; Nabil Khzam; Mahina L’Hostis; Georgios N. Belibasakis; Anders Johansson; Jan Oscarsson (Frontiers in Cellular and Infection Microbiology)
The Gram-positive organism Filifactor alocis is implicated in multiple oral diseases including periodontitis, and approximately 50% of known strains encode and produce a recently identified repeat-in-toxin (RTX) protein, FtxA, partly homologous to the Aggregatibacter actinomycetemcomitans leukotoxin. By assessing a longitudinal Ghanaian study population of adolescents, we recently identified a possible correlation between F. alocis levels, ftxA gene carriage, and progression of clinical attachment loss (CAL). To extend knowledge on the possible significance of F. alocis and its FtxA in periodontal disease, we have in the present work analyzed saliva samples in an independent cohort of periodontitis (n=156), collected at two private periodontal specialist practices in Perth, Western Australia. The present results corroborate that high loads of F. alocis and the presence of its ftxA gene together are associated with parameters of periodontal tissue destruction and severity. Moreover, among the individuals carrying A. actinomycetemcomitans, a majority also exhibited an ftxA-positive F. alocis, supporting the notion of the synergistic behavior of these two species. This emphasizes that F. alocis and its ftxA are involved in the pathogenesis of periodontitis and may have ecological roles, with diagnostic and prognostic implications for the disease.